Forward extrusion - possibilities of the process analysis - Plančak, Miroslav (Journal of Production Engineering, 1985)
This paper presents the load estimation in forward extrusion of steel using the visioplasticity method. This load is compared with: a) the upper bound solution b) the deformation work method and with the load obtained c) by experiment. Details of the visioplasticity method used are given. The difference between the obtained results is up to 30%. The most realistic value of the load (the one closest to the experimental load) is obtained using the visioplasticity method. Nevertheless, this method is suitable for more complex studies, such as strain and stress analysis, process kinetics, etc. For simple load estimates, visioplasticity is too complicated and time consuming.